Knowledge, attitudes, and practices (KAPs) on agrochemical use in small-scale farmers near Lake Tana, Ethiopia: Impacts on public and aquatic ecosystem health - Balew Yibel Zeleke; Andualem Mekonnen Hiruy; Ermias Deribe Weldemariam; Seblework Mekonen Shegen; Tesfa Aklilu (PLoS ONE, 2026)
Agrochemical application is essential for increasing agricultural production and achieving Sustainable Development Goal 1 to secure worldwide hunger. In Ethiopia, there is haphazard use of pesticides for agricultural intensifications. However, knowledge, attitudes, and practices (KAPs) regarding agrochemical use vary globally, especially in developing countries. This inconsistency raises significant concerns for human health and environmental degradation. Therefore this study aimed to assess the KAP of agrochemicals among communities surrounding Lake Tana. A community-based study was conducted targeting 352 small-scale farmers in selected villages, categorized by four regimes. Data were collected through face-to-face interviews and in situ observations via a pretested and semi structured questionnaire. The data were analyzed via chi-square tests and logistic regression. The findings revealed that, 100% of the respondents used pesticides on their farm, 42.3% had good knowledge, 56.5% had a positive attitude, and only 22.4% practiced well. The majority (57.1%) used banned pesticides particularly DDT, and 39% repurposed empty pesticide containers for household use. Moreover, 69% and 17% of the respondents reported that they most commonly use class II (moderately hazardous), and class III (slightly hazardous), respectively. Literate respondents were 2.329 times more likely to practice good pesticide application than illiterate respondents were (AOR = 2.329, Cl = 1.228, 4.419). The educational level and attitudes of the respondents showed significant associations with pesticide application practices according to binary logistic regression, with a P value <0.05. Poor pesticide practices were more prevalent in the Dembia and Fogera plain regimes than in the Bahirdar and Gilegel Abay regimes. Education and location (study clusters) were key factors, highlighting the need for capacity building and enforcement to protect the community and the aquatic ecosystem.